A poética radical no modernismo brasileiro: a "Experiência nº 2" de Flávio de Carvalho - Oliveira, Simone Aparecida de (2008)
This dissertation intends to contribute to the historic analysis of the proposal for the visual arts revival in São Paulo during the period comprehending the Brazilian modernism, through the discussion and analysis of Flávio de Carvalho modern artistic proposal. Through the examination of the pictorial, architectonical and specially the realization of the Experiment n. 2 by Flávio de Carvalho, main focus of this research, it was possible to establish the essential intersection and the diversion points between the proposal for artistic renewal imagined by the paulista modernists of that period of time, specially characterized by the representation of the Brazilian mannerism and the proposal of artistic revival idealized by Flávio de Carvalho, who searched for the rupture of this pursuit in his artistic production attentive to the comprehension of the city as the irradiation center of the vanguard movements and the modernity contradictions. The analysis of the Experiment n. 2 by Flávio de Carvalho in this dissertation intends to investigate its depiction as the vertex of an artistic revival in São Paulo which marked the insertion of the urban space in the artistic creation process and brought some concepts of the Dadaist and surrealist vanguard to the paulistano atmosphere during the decade of 1930